2023
DOI: 10.3389/fpubh.2022.914548
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between physical activity, physical health, and mental health among older Chinese adults: A scoping review

Abstract: The aging Chinese population is growing fast, and the proportion of the population aged 60 years old is projected to reach 28% by 2040, estimated 402 million. With increased life expectancy, the aging population tends to suffer from health risks and diseases, which create a burden on public health policy. Hence, it is essential to promote healthy and active aging, which includes improving older adults' physical and mental capacities and advocating for the achievement of a healthy life expectancy. Despite the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 107 publications
2
15
0
Order By: Relevance
“…Physical activities were negatively related to depressive symptoms, anxiety symptoms, and negative affect, while positively linked to life satisfaction and positive affect. These findings resonate with previous literature that established the positive influence of physical activities on mental and subjective well‐being outcomes, suggesting a consistent trend even during the pandemic 25 …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Physical activities were negatively related to depressive symptoms, anxiety symptoms, and negative affect, while positively linked to life satisfaction and positive affect. These findings resonate with previous literature that established the positive influence of physical activities on mental and subjective well‐being outcomes, suggesting a consistent trend even during the pandemic 25 …”
Section: Discussionsupporting
confidence: 91%
“…These findings resonate with previous literature that established the positive influence of physical activities on mental and subjective well-being outcomes, suggesting a consistent trend even during the pandemic. 25 Recreational activities were negatively associated with anxiety symptoms, indicating their potential as nonpharmacological interventions in reducing anxiety among older adults. This aligns with the "distraction hypothesis," which suggests that engaging in recreational activities could distract individuals from stressors, thus reducing anxiety.…”
Section: Discussionmentioning
confidence: 94%
“…Obesity is associated with the development of many diseases such as atherosclerosis, type 2 diabetes, and dyslipidemia, and has become a global epidemic and public health crisis (7,8). Previous studies have reported that chronic diseases caused by physical inactivity and obesity not only have a serious negative impact on the physical and mental health of individuals but also create a heavy burden on social development (9)(10)(11)(12). Therefore, WHO and professional health agencies expect to develop active and effective intervention policies to help people improve their PA and adopt healthy weight.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, to attract more older adults to participate in outdoor sports consistently and persistently, the plans should meet the needs of China’s aging society and take account of older adults’ motivation and demand for outdoor sports programs, venues, services, and products. 4 …”
Section: Introductionmentioning
confidence: 99%